Pengaruh Motivasi terhadap Interaksi Persepsi dan Partisipasi Siswa Sekolah Dasar yang Berstatus Broken Home di SDN Gugus 4 Kecamatan Ampenan - Laili Mutmainnah; Husniati; Mohammad Archi Maulyda (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to analyze the influence of learning perception on the learning participation of elementary school students from Broken Home backgrounds, while also examining the role of learning motivation as both a mediating and moderating variable. A quantitative approach with explanatory research design was employed. The research subjects consisted of 167 students at SDN Gugus 4 Ampenan District, selected through a purposive sampling technique. Data were collected using questionnaires that had been tested for validity and reliability, and subsequently analyzed using regression, mediation analysis, moderation analysis, and ANCOVA. The results indicated that learning perception had no significant direct effect on learning participation (Sig. = 0.704 > 0.05). However, learning perception had a significant effect on learning motivation, and learning motivation had a significant effect on learning participation (Sig. < 0.001). Learning motivation was proven to function as a full mediator but did not serve as a moderating variable (Sig. = 0.358 > 0.05). The ANCOVA test results showed that gender and age variables had a significant influence on learning participation (Sig. < 0.05), whereas the type of Broken Home background did not show a significant effect (Sig. = 0.639 > 0.05).